Elemental Characteristics and Source-Apportionment of PM2.5 During the Post-monsoon Season in Delhi, India - Bangar, Vaibhav; Mishra, Amit Kumar; Jangid, Manish; Rajput, Prashant (Frontiers in Sustainable Cities, 2021)
In this study, we have coupled measurements, modeling, and remote sensing techniques to better delineate the source characteristics and variability of air pollutants in Delhi primarily during the post-monsoon season in 2019. We show a comparison of ambient PM2.5 (particulate matter having aerodynamic diameter ≤2.5 μm) levels and associated elements during the post-monsoon with those during a relatively clean season of monsoon (experiencing frequent wet precipitation). Air-mass back trajectories from Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model have been used to infer the possible source pathways of PM2.5 impacting at the receptor site in Delhi. The average concentrations of PM2.5 during monsoon (June–July) and post-monsoon (October–November) were 42.2 ± 15.5 μg m−3 (range: 22–73 μg m−3) and 121.4 ± 53.6 μg m−3 (range: 46–298 μg m−3), respectively. The PM2.5 samples were analyzed for heavy and trace elements (Si, S, Na, Mg, Al, Cl, Ca, K, Ti, V, Cr, Mn, Fe, Ni, Cu, Br, Rb, Zr, and Pb) using an Energy Dispersive X-ray Fluorescence (ED-XRF) technique and their concentrations have been used to carry out the source-apportionment utilizing principal component analysis (PCA) tool. The PCA analysis has identified three major sources of fine aerosols including contributions from the sources viz. vehicular emission, biomass burning, coal combustion, secondary aerosols formation, soil dust, solid-waste burning and industrial emission. The source involving biomass burning contributed largely to the PM2.5 in post-monsoon season through long-range transport of large-scale agriculture-residue burning emissions (occurring in the states of Punjab, Haryana, and western part of Uttar Pradesh). The industrial emissions include primarily, medium- and small-scale metal processing industries (e.g. steel sheet rolling) in Delhi-National Capital Region. Traces of emission from coal based thermal power plants and waste incineration have also been observed in this study.